COLLABORATIVE GOVERNANCE IN THE MANAGEMENT AND PROTECTION OF THE BATANGHARI RIVER BASIN IN JAMBI PROVINCE - Rayi Retriananda Maulana; Utang Suwaryo; Franciscus Van Ylst (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2023)
This study aims to outline an understanding of collaboration in the management and protection of the Batanghari watershed in Jambi Province. This research uses a qualitative description method, using a collaborative governance theory approach, an understanding of how stakeholders with different interests, strengths and weaknesses, depend on each other to achieve common goals. Work collectively by minimizing conflict. Conflicts are likely to occur especially when there is a need for resource sharing for the provision of services as part of implementation efforts. Nonetheless, a commitment to achieving the same goals is essential for collaborative governance. So that the key factors in the formation of collaboration are science, leadership and experience, besides internal factors are also very decisive such as political leadership and financial support. This study aims to outline an understanding of collaboration in the management and protection of the Batanghari watershed in Jambi Province. This research uses a qualitative description method, using a collaborative governance theory approach, an understanding of how stakeholders with different interests, strengths and weaknesses, depend on each other to achieve common goals. Work collectively by minimizing conflict. Conflicts are likely to occur especially when there is a need for resource sharing for the provision of services as part of implementation efforts. Nonetheless, a commitment to achieving the same goals is essential for collaborative governance. So that the key factors in the formation of collaboration are science, leadership and experience, besides internal factors are also very decisive such as political leadership and financial support.